Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Get immediate and reliable answers to your questions from a community of experienced experts on our platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
[tex](4x-2)*6(2x+7)=(4x-2)*(12x+42)[/tex] I can do this because of distribution, which I will use again in the following: [tex](4x-2)*(12x+42)=48x^2-24x+168x-84=48x^2+144-84[/tex]
This is the answer.
This is the answer.
(4x - 2)(6(2x + 7)) = 0
(4x - 2)(6(2x) + 6(7)) = 0
(4x - 2)(12x + 42) = 0
48x² + 168x - 24x - 84 = 0
48x² + 144x - 84 = 0
x = -144 +/- √(144² - 4(48)(-84))
2(48)
x = -144 +/- √(20,736 - 16,128)
96
x = -144 +/- √(4,608)
96
x = -144 +/- 67.88
96
x = -1.5 +/- 0.707083
x = -1.5 + 0.707083 x = -1.5 - 0.707083
x = -0.792917 x = -2.207083
(4x - 2)(6(2x) + 6(7)) = 0
(4x - 2)(12x + 42) = 0
48x² + 168x - 24x - 84 = 0
48x² + 144x - 84 = 0
x = -144 +/- √(144² - 4(48)(-84))
2(48)
x = -144 +/- √(20,736 - 16,128)
96
x = -144 +/- √(4,608)
96
x = -144 +/- 67.88
96
x = -1.5 +/- 0.707083
x = -1.5 + 0.707083 x = -1.5 - 0.707083
x = -0.792917 x = -2.207083
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.